FINTECH-BASED LENDING PLATFORM AWARENESS FRAMEWORK FOR MICROBUSINESS OWNERS IN NAGA CITY - Dimaculangan, Alexander (Jurnal Bisnis dan Keuangan, 2026)
This study investigated the adoption of financial technology (FinTech) lending platforms among microbusiness owners in Naga City, Philippines. Specifically, it determined the FinTech lending platforms adopted, in terms of provider choice, usage extent, and perceived loan characteristics; the factors influencing adoption; the challenges encountered; and the development of an awareness framework to support informed adoption. A mixed-method research design was employed, combining quantitative survey data and qualitative insights from open-ended responses. A total of 100 microbusiness owners who had applied for or received FinTech loans within the past 24 months were selected using quota sampling to ensure representation across business types and operational profiles. The findings showed that microbusiness owners selectively adopted FinTech lending platforms, but once adopted, they used these platforms extensively for essential financing activities. Usability emerged as the most influential adoption factor, and financial challenges were identified as the most significant challenge. The thematic analysis revealed persistent confusion about interest computation, loan terms, data privacy, and repayment policies, along with a strong demand for clearer explanations and educational support. Based on these findings, a FinTech awareness framework was developed to address identified knowledge gaps and support informed use of FinTech lending platforms. The study concluded that while FinTech lending platforms provide accessible financing options for microbusiness owners, effective adoption depends on clarity, trust, usability, and targeted financial education. The results contribute localized empirical evidence to the literature on digital financial inclusion and offer practical guidance for FinTech providers, policymakers, and microbusiness stakeholders.